An analysis of strategies to improve financial sustainability of revolving loan fund programs: a case of world vision Burundi hiv/aids project in gashoho adp - Macumi, Fabian (International Journal of Scientific Research and Management (IJSRM), 2023)
Financial sustainability for revolving loan fund programs has been a topic of utmost interest especially to most non-profit organization (NGO) leaders, potential funders, including those communities that these programs function for. Financial sustainability makes the basis for community development which combines interventions by development-workers both from governmental and non-governmental agencies. This study sought to investigate the strategies adopted to improve financial sustainability of funding programs that related to revolving loans with one singular case study of a World Vision Burundi HIV/AIDS project in Gashoho ADP. The study is used descriptive research design to seek opinion of respondents. Descriptive statistics and inferential statistics were used to evaluate and assess quantitative information whereas the thematic analysis was utilised to evaluate qualitative information. The study found that training on fund use, reduction of corruption, increasing awareness on vision of revolving loan funds, development of entrepreneurial mindset among beneficiaries, implementation of good financial management system, proper monitoring & evaluation of the performance of revolving loan fund programs as effective strategies for enhancing financial sustainability of revolving loan fund programs in Gashoho for enhancing financial sustainability of revolving loan funds in Burundi, Gashoho ADP. The study concluded that fund- use training was related to financial sustainability of revolving loan fund programs (r=.2017; R- square = 0.0408). The study showed that financial management is effective in ensuring the financial sustainability of revolving funds programs by increasing knowledge on the utilization of financial resources (r=0.08). Similarly, the study concluded that monitoring and evaluation is a key to achieving the financial sustainability of revolving loan funds programs(r=0.116; Chi- Square=0.008; and F-Statistic = 2.72 at significance level =.100). The study concluded that training on fund use, financial management practices and Monitoring and evaluation of projects as the key strategies for the financial sustainability of revolving funds. The study recommended that revolving funds adopts these tripartite strategies to ensure the revolving remain sustainable after the donor leaves the project.